2023
DOI: 10.1615/critreveukaryotgeneexpr.2022044300
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-485-3p Promotes the Inflammatory Response and Extracellular Matrix Deposition by Activating Wnt/β-Catenin Signaling in Human Airway Smooth Muscle Cells

Abstract: The aim of this study was to study the effects of microRNA (miR)-485-3p on the inflammatory response and extracellular matrix deposition of human airway smooth muscle cells (HASMCs). The levels of miR-485-3p and WIF1 in peripheral blood of pediatric asthma (PA) patients and controls were examined by quantitative real-time polymerase chain reaction (qRT-PCR). miR-485-3p inhibitor and mimic, together with negative control (NC) inhibitor/ mimic, were transfected into HASMCs treated with tumor necrosis factor (TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In atherosclerosis, miR‐485‐3p targets Olr1 to regulate vascular inflammation and lipid transport, thereby participating in the development of the disease 14 . In paediatric asthma, miR‐485‐3p can also promote inflammatory response and extracellular matrix deposition by activating the Wnt/β‐catenin signalling pathway in human airway smooth muscle cells 27 . To uncover the function of miR‐485‐3p in AD, we conducted extensive research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In atherosclerosis, miR‐485‐3p targets Olr1 to regulate vascular inflammation and lipid transport, thereby participating in the development of the disease 14 . In paediatric asthma, miR‐485‐3p can also promote inflammatory response and extracellular matrix deposition by activating the Wnt/β‐catenin signalling pathway in human airway smooth muscle cells 27 . To uncover the function of miR‐485‐3p in AD, we conducted extensive research.…”
Section: Discussionmentioning
confidence: 99%
“… 14 In paediatric asthma, miR‐485‐3p can also promote inflammatory response and extracellular matrix deposition by activating the Wnt/β‐catenin signalling pathway in human airway smooth muscle cells. 27 To uncover the function of miR‐485‐3p in AD, we conducted extensive research. At the cellular level, we found that overexpression of miR‐485‐3p in HAVSMCs led to heightened inflammation and increased apoptosis, while downregulation of miR‐485‐3p suppressed these processes.…”
Section: Discussionmentioning
confidence: 99%